Quantum Dot Parity Effects in Trivial and Topological Josephson Junctions - Razmadze, D.; O'Farrell, Eoin; Krogstrup, Peter; Marcus, Charles (Physical Review Letters, 2020)
An odd-occupied quantum dot in a Josephson junction can flip transmission phase, creating a [π] junction. When the junction couples topological superconductors, no phase flip is expected. We investigate this and related effects in a full-shell hybrid interferometer, using gate voltage to control dot-junction parity and axial magnetic flux to control the transition from trivial to topological superconductivity. Enhanced zero-bias conductance and critical current for odd parity in the topological phase reflects hybridization of the confined spin with zero-energy modes in the leads.